2000
DOI: 10.1002/(sici)1522-726x(200003)49:3<258::aid-ccd7>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous transluminal coronary angioplasty of chronic total occlusions. determinants of primary success and long-term clinical outcome

Abstract: This study was conducted to assess the determinants of the procedural success and long‐term clinical benefits of percutaneous transluminal balloon angioplasty (PTCA) of chronic total occlusion (CTO) in recent years. Two hundred and twenty‐six consecutive patients who underwent PTCA of CTO were divided into two groups according to the procedural success (n = 134) or failure (n = 92). Both groups were analyzed in terms of the initial success, predictors of procedural failure, and clinical outcome. The procedural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
137
7
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(158 citation statements)
references
References 20 publications
10
137
7
4
Order By: Relevance
“…Mollet et al also reported that CTO lesion length > 15 mm measured on CT was associated with higher failure rate of PCI . Heavy calcification of CTO has been reported to be an independent predictor of failed PCI of CTO (Noguchi et al, 2000). The exact location of calcified plaque on the image of coronary CT angiography may help the interventionist to steer the guide wire away from the calcified lesion that is not well seen on conventional angiography.…”
Section: Total Occlusionsmentioning
confidence: 99%
“…Mollet et al also reported that CTO lesion length > 15 mm measured on CT was associated with higher failure rate of PCI . Heavy calcification of CTO has been reported to be an independent predictor of failed PCI of CTO (Noguchi et al, 2000). The exact location of calcified plaque on the image of coronary CT angiography may help the interventionist to steer the guide wire away from the calcified lesion that is not well seen on conventional angiography.…”
Section: Total Occlusionsmentioning
confidence: 99%
“…High procedural success rates in conjunction with low complication rates improve risk/beneit ratio and are paramount for the acceptance and dissemination of CTO PCI. Successful CTO recanalization has the ability to relieve angina [71], reduce ischemia [41] and the need for CABG [72], improve exercise tolerance [73], electrical stability [74], left ventricular function [44], and tolerance of future ACS [13,75], and possibly survival [76,77] with a similar risk compared to regular PCI of non-CTO lesions [3]. Table 1 summarizes the rationale for CTO PCI.…”
Section: Indications For Cto Pcimentioning
confidence: 99%
“…Traditional predictors for CTO PCI failure are increasing age of the occlusion, small vessel diameter, presence of calcium or a blunt stump, proximal cap ambiguity, excessive tortuosity, long occlusion length, bridging collaterals, and absent visibility of the distal vessel [72,89,[92][93][94][95]. Furthermore, these lesions show a higher mean Multicenter CTO Registry of Japan (J-CTO) score and have collaterals that are less likely suitable for the retrograde approach [96].…”
Section: Procedural Success In Patients With Cto Undergoing Pci or Cabgmentioning
confidence: 99%
“…In fact, we reported that successful coronary angioplasty for patients with chronic total occlusion conferred favorable long-term outcomes. 17 Thus, a higher degree of stenosis is a disadvantage for long-term survival in ischemic heart disease, and revascularization of such coronary arteries may have an advantage for long-term survival. This also may be related to the 'open-artery hypothesis'.…”
Section: Lad and Long-term Prognosis In Non-diabetic Patientsmentioning
confidence: 99%